Latinas attempting suicide when cultures, families, and daughters collide - Zayas, Luis H. (New York ; Oxford : Oxford University Press, 2011)
Among teenage Latinas in the United States, suicide attempts occur at rates sometimes twice as high as other youth. This book looks into the development of young Latinas, girls caught between two cultures, struggling to reconcile them.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Hispanic American teenage girls -- Suicidal behavior; Youth -- Suicidal behavior -- United States